Systemwide efforts to improve student achievement - Wong, Kenneth K., 1955-; Rutledge, Stacey A. (Research in educational policy., 2006)
Strong system-wide support is increasingly being identified as laying an important role in policy efforts aimed at increasing student achievement (Hightower, Knapp, March, and McLaughlin: 2002). Yet current research often views district and other system-wide support as largely governance changes without substantive linkage to school improvement outcomes (Cuban and Usdan: 2003). In this volume we seek to deepen our understanding of the role of school districts and system-wide initiatives through a series of case studies that focus on how school districts and system-wide actors facilitate policy innovation and reform initiatives that are designed to improve student achievement. Through both quantitative and qualitative studies from diverse settings across the country, chapters in this volume examine the role of instructional technology, alternative accountability practices, management and partnership reforms, and school improvement efforts through new incentive and support practices. While challenges remain, these case studies demonstrate how districts support and facilitate school change aimed at improving student achievement.